Standardization of Virgin Mojito Mocktail Beverages in Sebungkus Indonesia - Cahyadi Kang, Alfito Dimas; Lise Asnur (Journal of Multidimensional Management, 2025)
The food and beverage industry increasingly emphasizes innovation and consistency to ensure consumer satisfaction and operational efficiency. Within this context, mocktails such as the Virgin Mojito are gaining popularity due to their refreshing sensory attributes and health-related benefits, yet inconsistent preparation often reduces customer satisfaction. This study aimed to develop a standardized Virgin Mojito recipe at Sebungkus Indonesia to ensure uniform quality across different preparations. The research employed an experimental design by comparing two formulations—one currently used at Sebungkus Indonesia and one adapted from literature—followed by refinement into a gram-based standardized recipe. Sensory evaluation was conducted by three expert panelists using a hedonic scale across six indicators: acidity, sweetness, aroma, colour, balance, and presentation. The results showed that the Sebungkus Indonesia recipe performed better than the literature-based version, and after refinement, the standardized recipe achieved an overall mean score of 3.66 (“highly liked”), representing a significant improvement from the initial 2.83 (“liked”). The highest increase was recorded in aroma (4.00), while presentation and colour also contributed substantially to acceptance. These findings highlight that precise measurement and process standardization enhance beverage quality, reduce variability, and strengthen consumer satisfaction. The study contributes practically by providing Sebungkus Indonesia with a reliable recipe for consistent service, and theoretically by demonstrating the strategic role of recipe standardization in quality management and competitiveness within the hospitality sector.